The 19th-century missionary literature: Biculturality and bi-religiosity, a reflection from the perspective of the wretched - Mothoagae, Itumeleng D. (HTS teologiese studies, 2024)
The 19th-century missionary literary genre provides us with a window into how the missionaries viewed African cultural systems, such as polygamy. In their minds, polygamy was one of the obstacles to converting Africans to Christianity. Baptism functioned as a theatre of power and submission. To access baptism, a convert had to abandon and strip themselves of that which made them Africans and adopt Western colonial Christian norms and principles. In this article, we argue that the condemnation of polygamy by missionaries was a wielding of power within the colonial matrix of power. We further maintain that the decolonisation of Christianity cannot be achieved without a critical analysis of the impact of the missionaries in the deformation and labelling of African cultural identities as heathen and uncivilised.Contribution: The cultural transfer that was achieved through Christianisation, civilisation and colonisation has led to what Biko referred to as the flight from the black self and what Du Bois referred to as double consciousness. The article applies the intersectionality of theoretical lenses of Africana critical thought, Foucauldian notion of power, negritude and decoloniality.